PELATIHAN âCREATIVE PARENTING TODAYâ CARA PRAKTIS MEMICU DAN MAMACU KREATIVITAS DAN PRIBADI ANAK MELALUI POLA ASUH KREATIF BAGI ORANG TUA DI CABENGE KABUPATEN SOPPENG - A., Anriani; R., Riska; I., Irmayanti (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Parenting style is one of the significant factor that helped to profile the children. This is based on assumption that education in the family is the first and primary education obtained by children, which is cannot be replaced by any other institution. For instance children superkids models they were displaced from their childhood, and as adults they will be adults but still childish. So parenting parents largely determines the attitude and the nature of his future. To that end we strive to provide training to parents in the district Cabbenge Soppeng to be